2011
DOI: 10.1073/pnas.1101042108
|View full text |Cite
|
Sign up to set email alerts
|

A neural basis for real-world visual search in human occipitotemporal cortex

Abstract: Mammals are highly skilled in rapidly detecting objects in cluttered natural environments, a skill necessary for survival. What are the neural mechanisms mediating detection of objects in natural scenes? Here, we use human brain imaging to address the role of top-down preparatory processes in the detection of familiar object categories in real-world environments. Brain activity was measured while participants were preparing to detect highly variable depictions of people or cars in natural scenes that were new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
179
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(201 citation statements)
references
References 33 publications
9
179
1
Order By: Relevance
“…The activity of neurons in inferior temporal cortex (IT) that selectively respond to a particular object is enhanced in a sustained fashion while monkeys prepare to find this object in an upcoming search display (Figure 3a), and such preparatory "baseline shifts" of neural activity level may reflect an activated attentional template [7]. Similar target-selective preparatory activation patterns have been found in human event-related brain potential (ERP) and fMRI experiments [8][9][10][11][12][13][14]. Some fMRI studies have demonstrated increased activity in colour-or motion-selective visual areas when observers prepare for targets defined in these dimensions [9][10][11].…”
Section: Preparationmentioning
confidence: 58%
See 3 more Smart Citations
“…The activity of neurons in inferior temporal cortex (IT) that selectively respond to a particular object is enhanced in a sustained fashion while monkeys prepare to find this object in an upcoming search display (Figure 3a), and such preparatory "baseline shifts" of neural activity level may reflect an activated attentional template [7]. Similar target-selective preparatory activation patterns have been found in human event-related brain potential (ERP) and fMRI experiments [8][9][10][11][12][13][14]. Some fMRI studies have demonstrated increased activity in colour-or motion-selective visual areas when observers prepare for targets defined in these dimensions [9][10][11].…”
Section: Preparationmentioning
confidence: 58%
“…Although spatially global working memory representations do exist in visual cortex [15], the question whether preparatory goalselective patterns of visual activity are generally position-invariant, and whether this is a necessary requirement for their role as attentional templates still needs to be systematically addressed. 5 In line with the involvement of prefrontal cortex in visual working memory (Box 1), preparatory activation patterns that are sensitive to current task goals have also been observed in prefrontal areas [13,20,21]. These effects may be linked to top-down aspects of attentional preparation, with prefrontal cortex controlling target-selective preparatory modulations of visual activity, but could also reflect explicit representations of search goals.…”
Section: Preparationmentioning
confidence: 67%
See 2 more Smart Citations
“…Preparation for a specific target shape elicited a shape-selective pattern of neural activation in lateral occipital cortex during the interval before the target was presented (Stokes, Thompson, Nobre, & Duncan, 2009). Even search for categorydefined target objects in natural visual scenes (e.g., people or cars) was found to be preceded by preparatory category-selective activation patterns in visual cortex (Peelen & Kastner, 2011). …”
Section: Preparatory Attentional Templates and Visual Working Memorymentioning
confidence: 99%